PhD proposal (BAA Doctoral Colloquium Cardiff 2010): short selling and stock returns - Mohamad, Azhar (2010)
Short selling arguably is one of the most controversial issues in stock market, and is often blamed for stock market crash. There are negative preconceptions among media and market regulators regarding short selling. Short interest data is not publicly available in most stock markets around the world. Besides the United States of America, Hong Kong is the only jurisdiction that makes short interest data available to investing public. While most studies on short interest and stock returns have focused on the US stock markets, there are very few studies done on the Hong Kong stock market. So the main motivations of this paper are: a) To investigate the relationship between short interest and stock returns in Hong Kong stock market b) To examine whether stock abnormal returns increase in the level of short interest c) To examine the relationship between level short interest and fundamental-to-price ratios and institutional ownership of shorted stocks